Molecular biomethods handbook - Rapley, Ralph; Walker, John M (Humana Press, 1998)
Univ. of Hertfordshire, Hatfield, UK. Introduces a selection of analytical and preparative techniques that are most frequently used by research workers in molecular biology. The theory and application of these techniques are explained. For undergraduate students and researchers. Well-referenced with halftone illustrations.
Keywords: Molecular Biology; molekulární biologie; referenční knihy; biologie; Reference Books